P53 Determination of specific IgE antibodies to mouse proteins in laboratory animal workers. (12th November 2015) - Canizales, J; Welch, J; Fitzgerald, B; Lightfoot, Z; Banya, W; Feary, J; Cullinan, P; Jones, M
Abstract : Introduction: Laboratory animal workers are at increased risk of developing specific IgE antibodies to laboratory animal proteins. The major allergen for mouse is Mus m 1 which is predominantly found in the urine. Specific IgE to mouse is determined using either a commercial skin prick test solution of mouse epithelium or ImmunoCAP for either mouse urine or epithelium. Specific IgE to Mus m 1 is used for routine diagnostic testing. The aim of this study was to compare sensitisation using both ImmunoCAP and skin prick test as well as compare mouse urine and epithelium as allergens. At present there is no gold standard for sensitisation to mouse allergens. Methods: Laboratory workers exposed to mice were recruited to the SPIRAL (Safe Practice in Reduction of Allergy in Laboratories) study. Sensitisation was determined by the presence of specific IgE to Mus m 1 and mouse epithelium using ImmunoCAP (Phadia) (positive result ≥0.35 kU/l) and by skin prick test to mouse epithelium (positive result is a saline adjusted mean wheal diameter of ≥3 mm). Results: Of the participants (321), 11 (3%) were positive by skin prick test, 34(11%) with specific IgE to Mus m 1 and 35 (11%) with a positive specific IgE to mouse epithelium. There were 25/321(8%) participants with a discordant results between SPT and specific IgE to Mus m 1 (Table 1 ). There were 14 participants with a discordant result between specific IgE to Mus m 1 and mouse epithelium (Table 1 ). Discussion: Laboratory animal workers may have specific IgE antibodies to either Mus m 1 or mouse epithelium. Diagnostic tests for mouse sensitisation may require testing to both Mus m 1 and mouse epithelium to ensure we do not miss any sensitised cases. Skin prick tests appear higher rates of false negative than anticipated and are therefore less reliable in clinical practice if used alone.